Obstructive sleep apnea, health-related factors and long-distance heavy vehicle crashes in Western Australia: a case control study. - Meuleners, Lynn; Fraser, M.; Govorko, M.; Stevenson, M. (2015)
Study Objectives: To determine the association between obstructive sleep apnea (OSA), health-related factors and the likelihood of heavy vehicle crashes in Western Australia (WA). Methods: This case-control study included 100 longhaul heavy vehicle drivers who were involved in a police reported crash in WA during the study period (cases) and 100 long-haul heavy vehicle drivers recruited from WA truck stops, who were not involved in a crash during the past year (controls). Driver demographics, health, and fatigue related characteristics were obtained using an interviewer administered questionnaire. Drivers were tested for OSA using a diagnostic Flow Wizard. Logistic regression was used to determine health-related factors associated with crash involvement among long distance heavy vehicle drivers. Results: Heavy vehicle drivers diagnosed with OSA through the use of the FlowWizard were over three times more likely to be involved in a crash than drivers without OSA (adjusted OR: 3.42, 95% CI: 1.34–8.72). The risk of crash was significantly increased if heavy vehicle drivers reported a diagnosis of depression (adjusted OR: 6.59, 95% CI: 1.30–33.24) or had not completed fatigue management training (adjusted OR: 6.05, 95% CI: 1.80–20.24). Crash risk was 74% lower among older drivers (> 35 years) than younger drivers (adjusted OR: 0.25, 95% CI: 0.08–0.82).The results suggest that more rigorous screening and subsequent treatment of OSA and depression by clinicians as well as compulsory fatigue management training may reduce crashes among heavy vehicle drivers.